Berberine Protects Against Simulated Ischemia/Reperfusion Injury-Induced H9C2 Cardiomyocytes Apoptosis In Vitro and Myocardial Ischemia/Reperfusion-Induced Apoptosis In Vivo by Regulating the Mitophagy-Mediated HIF-1α/BNIP3 Pathway - Zhu, Na; Li, Jiang; Li, Yongli; Zhang, Yuwei; Du, Qiubo; Hao, Peiyuan; Li, Jinying; Cao, Xueming; Li, Li (Frontiers in Pharmacology, 2020)
Berberine (BBR) has a variety of pharmacological activities and is widely used in Asian countries. This study aimed to investigate the protective mechanism of BBR against myocardial ischemia-reperfusion injury (MIRI) and establish a scientific basis for the clinical application of BBR. In vitro experiments, BBR pretreatment regulated autophagy-related protein expression, induced cell proliferation and autophagosome formation, and reduced the mitochondrial membrane potential (ΔΨm) increase in H9C2 cells. In vivo experiments, BBR reduced the myocardial infarct size, decreased cardiomyocyte apoptosis, and markedly decreased myocardial enzyme (CK-MB, LDH and AST) activity-induced I/R. In addition, upon BNIP3 knockdown, the regulatory effects of BBR on the above indicators were weakened both in H9C2 cells and in vivo. Luciferase reporter and ChIP assays indicated that BBR mediated BNIP3 expression by enhancing the binding of HIF-1α to the BNIP3 promoter. BBR protects against myocardial I/R injury by inducing the mitophagy-mediated HIF-1α/BNIP3 pathway. Thus, BBR may serve as a novel therapeutic drug for myocardial I/R injury.